2014
DOI: 10.1371/journal.pone.0111440
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width and Other Red Blood Cell Parameters in Patients with Cancer: Association with Risk of Venous Thromboembolism and Mortality

Abstract: BackgroundCancer patients are at high risk of developing venous thromboembolism (VTE). Red cell distribution width (RDW) has been reported to be associated with arterial and venous thrombosis and mortality in several diseases. Here, we analyzed the association between RDW and other red blood cell (RBC) parameters with risk of VTE and mortality in patients with cancer.MethodsRBC parameters were measured in 1840 patients with cancers of the brain, breast, lung, stomach, colon, pancreas, prostate, kidney; lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 38 publications
0
58
0
4
Order By: Relevance
“…The cumulative probability of survival in patients with high RDW (>16%) was 78.5% after 6 months, 66.2% after 1 year and 41.3% after 2 years. In comparison, patients with RDW levels ≤16% had a cumulative survival probability of 88.7% after 6 months, 75.1% after one year and 66.2% after 2 years (Log-rank P<0.001) (12). The authors observed that high RDW was associated with an increased risk of cancer-related mortality (HR, 1.72; 95% CI, 1.39-2.12; P<0.001), and this association persisted after adjustment for age, sex, hemoglobin, leukocyte and platelet count (HR, 1.34; 95% CI, 1.06-1.70; P=0.016).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The cumulative probability of survival in patients with high RDW (>16%) was 78.5% after 6 months, 66.2% after 1 year and 41.3% after 2 years. In comparison, patients with RDW levels ≤16% had a cumulative survival probability of 88.7% after 6 months, 75.1% after one year and 66.2% after 2 years (Log-rank P<0.001) (12). The authors observed that high RDW was associated with an increased risk of cancer-related mortality (HR, 1.72; 95% CI, 1.39-2.12; P<0.001), and this association persisted after adjustment for age, sex, hemoglobin, leukocyte and platelet count (HR, 1.34; 95% CI, 1.06-1.70; P=0.016).…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have demonstrated that RDW is higher not only in patients affected by CVD but also in patients affected by solid tumors and hematological cancer compared to healthy individuals (12)(13)(14). As well as mortality, in these patients increased RDW has been shown to predict advanced stage and worse prognosis (15).…”
Section: Introductionmentioning
confidence: 99%
“…Son yıllarda popüler olmaya başlayan özellikle çeşitli kanser tiplerinin sağ kalım sürelerinin tayin edilmesinde preoperatif dönemde elde edilen hematolojik parametrelerin preoperatif operabiliteyi veya metastatik hastalığı saptamakta faydalı olup olmayacağı araştırılmaya başlan-mıştır. Bu hematolojik parametreler içerisinde en sık çalışılanları nötrofil/lenfosit oranı (NLO), eritrosit dağılım genişliği (RDW) ve platelet/lenfosit oranıdır (PLO) [7][8][9] . RDW, kırmızı kan hücrelerinin (RBC) boyut ve hacim değişkenliğini gösteren ve anizositozu işaret eden parametredir.…”
Section: Girișunclassified
“…Yılmaz ve arkadaşları RDW'yi pankreas kanserinde morbidite ve mortaliteyi öngörmede, kolay ulaşılabilir, ucuz ve basit bir prediktif belirteç olarak bildirdiler 21 . Riedl ve arkadaşları ise, yüksek RDW düzeyle-rinin yanında artmış RDW ile birlikte görülen klinik durumlardan biri olan aneminin kanser sağ kalımında kötü prognostik faktör olduğu sonucuna vardılar 8 . Patel ve arkadaşları her %1'lik RDW artışına karşılık, mortalitede %14 artış bildirdiler, ancak bu artışın ileri yaş ve hemoglobin konsantrasyonuna bağlı olduğunun altını çizdiler 22 .…”
unclassified
“…This suggests that RDW may represent an erythrocyte value for early identification of cases of masked anemia (e.g., dehydration). It has been suggested in several human medical studies (RIEDL et al, 2014;TSELIOU et al, 2014;SALVAGNO et al, 2015) that such alterations may be due to other diseases in addition to anemia masked by dehydration; this remains unproven in domestic species (GUGLIELMINI et al, 2013;SWANN et al, 2014). According to Salvagno et al (2015), an increase in RDW reflects a breakdown in erythrocyte homeostasis involving both impaired erythropoiesis and survival of abnormal red blood cells.…”
Section: Introductionmentioning
confidence: 99%